(untitled) (Revista Logos Ciencia & Tecnología, 2019)
This study analyzed factors associated with career choice of police agents of Honduras. This was carried out using a mixed methods approach, combining focus groups and questionnaires in a sample of 828 police candidates. Results indicate three main motivational dimensions: pursuit of socioeconomic stability, community service and the social influence from family-friends. Other factors that motivate the permanency are the social links created between applicants, time and effort investment, and the opportunities for professional-academic development. Findings indicate that the available working conditions perceived in the informant’s home community are related to economic motivations regarding socioeconomic stability, but not with motivations related to community service. Additionally, the perception of violence isn’t related to the election of the police career